Tuning the surface charge and colloidal stability of hybrid gold-chitosan derivative nanoparticles for siRNA delivery - Martinez Júnior, André Miguel [UNESP] (2024)
In recent years, the therapeutic potential of small interfering RNA (siRNA) has been confirmed by the emergence of commercially available siRNA-based drugs and by advances in the clinical trials phase. However, the many biological barriers faced by siRNA up to its delivery to the intended target make the advances in siRNA therapies highly dependent on the use of efficient gene vectors. In this study, the design of a new nanoparticle structured with a gold core and a diisopropylethylamine-chitosan shell was devised for application as a siRNA carrier. Thiol functionalized diisopropylethylamine-chitosan polymers were grafted onto gold nanoparticles (AuNPs) to obtain pH-responsive hybrid siRNA carriers (AuNP@polymers). The precise control of the diisopropylethylamine (DIPEA) graft and the tuning of the amount of polymer linked to the AuNPs enabled the assembly of hybrid carriers with good colloidal stability in physiological ionic strength (150 mmol L−1), sizes between 50 and 100 nm and positive zeta potentials (up to +17 mV), over a wide range of pH (5.5–7.4). The coated AuNPs were able to bind siRNA at N/P ratios in the range of 5–20, providing protection for the siRNA against RNAse degradation and making the hybrid vectors structurally and colloidally stable even in a protein-supplemented medium. The AuNP@polymers nanocarriers displayed non-cytotoxic effects in both 3T3/NIH fibroblast and HeLa-GFP cells up to an N/P ratio of 20 and the uptake of AuNP@polymers by RAW 264.7 macrophages was similar to Lipofectamine™ RNAiMAX. The zeta potential of the hybrid vectors was accurately adjusted by controlling the DIPEA graft and the pH of the formulation medium, which in turn drove the silencing efficiency of the siRNA nanocarrier as observed by the green fluorescent protein (GFP) knockdowns in HeLa cells. GFP knockdown levels close to that of Lipofectamine (up to 70 %) were achieved for the vectors formulated at pH 5.5. Overall, the results showed that the DIPEA-chitosan/AuNP association is a promising strategy to formulate hybrid nanocarriers for siRNA delivery with potential for in vivo studies.